Implementation of Augmented Reality-Based Learning to Enhance Student Engagement and Achievement at SMA Hang Tuah Makassar - Muh Riyaldi Pratama; Kamaruddin Kamaruddin; John James (Yayasan Cendekiawan Digital Indonesia, 2026)
The development of digital technology in education demands learning innovations that can increase student engagement and understanding. This community service activity aims to implement Augmented Reality (AR)-based learning media to improve the quality of learning at Hang Tuah Senior High School, Makassar. The method used is a collaborative, participatory approach that follows the stages of needs identification, media development, training, implementation, and evaluation. AR media allows students to interact with three-dimensional objects, creating a more interactive and contextual learning experience. The results of the activity show an increase in student learning outcomes, with the average score rising from 54.43 to 83.36 and a gain of 0.65, which falls within the high category. In addition, there was an increase in student engagement and motivation to learn, as well as in teacher competence in integrating technology into learning. Despite obstacles such as limited devices and internet connectivity, the implemented adaptive strategy supported the program's success. The use of AR has the potential to be an innovative solution in supporting interactive and sustainable learning in the digital era. This research provides a practical contribution to the application of Augmented Reality-based learning in secondary education.